Influence of site of impact on cognitive impairment persisting long after severe closed head injury - Smith, Eileen (1974)
The cognitive abilities of right-handed men who had sustained a severe closed head injury between 10 and 20 years earlier were studied. Results showed that a right-sided impact produced greater deficits than a left-sided impact in both verbal and non-verbal skills. The results are interpreted as reflecting left hemisphere damage due to contrecoup injury. Some evidence that a left frontal impact was apt to result in defective visual-spatial functioning is presented. These observations accord with some theories on the mechanics of head injury and with observations on the predictability of sites of cerebral contusion in brain injury uncomplicated by dural penetration, intracranial infection, or cerebral infarction. The roles of the duration of post-traumatic amnesia, the level of neurological responsiveness at the time of admission to hospital, and the age at which the injury was sustained are also discussed.